The Compliance of Health Workers Doing Five Moments Of Handwashing With The Incidence Of Nosocomial Infections: Literature Review - Zulkarnain, Eva Vera; Muhith, Abdul; Chilyatiz (Journal of Applied Nursing and Health, 2024)
Background: Nosocomial infection is a cross-infection in nurses or patients during hospital treatment. One of the factors that can prevent nosocomial infections is health workers' compliance in carrying out 6 (six) hand washing steps. This literature review aims to determine the relationship between the compliance of health workers washing hands and the incidence of nosocomial infections in hospitals. Methods: The method used in this article is a literature review using the PRISMA Approach. Journal databases from Science Direct, PubMed, and Google Scholar in the  2019-2023 time frame. Keywords "Handwashing," "Five Moments," and "Healthcare-Associated Infections (HAIS)" from the identification results based on inclusion criteria and eligibility review obtained ten articles for review. Results: The literature review study found that adherence to five moments of hand washing significantly affected the prevention of nosocomial infections. Conclusion: It is expected that all health personnel who provide health services to patients with complete self-awareness are disciplined to carry out five moments of hand washing.